A Heuristic Solution Technique to the Joint Replenishment Problem with Quantity Discounts and Full Truck Loads - Al-Qaq, Mohammed (2014)
In this project a stochastic multi-item inventory problem is considered. A wholesaler buys multiple products, with stochastic demand and similar holding and purchase costs, from a single supplier. The supplier offers an all-unit quantity discount whenever a full truckload is replenished. For the delivery of the products trucks with a finite capacity are available. The dispatched trucks arrive at the wholesaler after a constant leadtime and with each truck fixed shipping costs are charged independent on the number of units shipped. Since fixed transportation costs are high coordination of orders and full truckload shipments can benefit from economies of scale and quantity discounts. A new heuristic solution to this problem is proposed. The solution includes a direct grouping strategy and considers the optimal solution from both, the shipping trucks and products perspectives. In implementing the proposed solution an adjusted periodic review system is used. An excellent performance of the proposed solution can be observed when the fixed cost per order is high and the demand of the different products is similar. While the proposed solution presented in this project to the joint replenishment problem under consideration has been shown to be reliable, it nevertheless represents the first step towards the development of more efficient and versatile future solutions to the problem.